Probing Into Identity Crisis In “Dark They Were And Golden-Eyed” Short Story - Ahmad, Muntazir; Batool, Saima (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
The present research is about the Postcolonial study of Ray Bradbury's short story "Dark They Were, and Golden-Eyed." Further, this research explores the issue of identity in the short story presented by the author. In the modern world, with the increase in immigrant numbers and the constitution of countries with different cultural diversities, identity issues arise. The researchers discuss the issue of identity in the postcolonial world and how the theorists viewed and presented their ideas about constructing identity in immigrants from these countries who suffered from facing the Diasporas and the dilemma of the difficulty of growing their identity. Furthermore, the paper investigates postcolonial novelists, especially in the novel "Dark They Were and Golden-Eyed ."As postcolonial theorists considered the issue of identity as one of its essential discussions, novelists also exposed the conditions of identity crises that emerged in the postcolonial period. Therefore, the method undertakes to apply postcolonial theories to the above novel, Dark They Were and Golden-Eyed. Different aspects and elements of Post Colonialism have been described in the research to explore the Post Colonialism presented in the novel, like ambivalence, racism, otherness, and hybridity.